Wonder : from emotion to spirituality - Fuller, Robert C., 1952- (The University of North Carolina Press, 2006)
In an exploration that bridges science and spirituality, the author makes the convincing case that a sense of wonder is a principal source of humanity's belief in the existence of an unseen order of life. He draws on the natural and social sciences to explain how wonder can elicit belief in the existence of a more-than-physical reality.